Fractional Oscillatory Integral Operators and Their Commutators on Generalized Orlicz-Morrey Spaces of the Third Kind - Eroglu, Ahmet (Eurasian Mathematical Journal, 2017)
We deal with the generalized Orlicz-Morrey space \(M_Φ,φ\) of the third kind and consider the boundedness of the oscillatory integral operators and fractional oscillatory integral operators on \(M_Φ,φ\). Some integral estimates for generalized Orlicz-Morrey spaces of the third kind are also obtained by using weighted Hardy operators. The corresponding commutators generated by \(BMO\)-functions are also considered.